Transformational and Transactional Leadership Styles as a Predictor of Individual Outcomes - Azman ISMAIL (Theoretical and Applied Economics, 2010)

(untitled)
This study was conducted to measure the relationship between transformational and transactional leadership styles and individual outcomes (i.e., perceptions of justice and trust in the leaders) using 118 usable questionnaires gathered from employees who have worked in a US subsidiary firm in East Malaysia, Malaysia. The results of exploratory analysis confirmed that the measurement scales used in this study met the acceptable standards of validity and reliability analyses. Further, the outcomes of Pearson correlation analysis showed six important findings: first, transformational leadership significantly correlated with procedural justice. Second, transactional leadership significantly correlated with distributive justice. Third, transformational leadership significantly correlated with trust in the leaders. Fourth, transactional leadership significantly correlated with trust in the leaders. Statistically, this result confirms that transformational leadership is an important predictor of procedural justice, transactional is an important predictor of distributive justice, and both leadership styles are important predictors of trust in the leaders. In addition, implications and discussion are elaborated.